Challenges to Design of the North Bypass Road of Shanghai and Innovative Technology. (2016) - Yu, Mingjian; Luo, Jianhui; You, Kesi; Fan, Yiqun
Abstract: With the increasing urbanization of China, more and more different types of underground roads have been completed or are under construction across Chinese cities and their scale keeps increasing too. The North Bypass Road of Shanghai, currently under construction, is the largest-scale underground urban road in China. Considering its location in the downtown area with a high concentration of buildings and population and the existence of numerous construction restrictions, its design and construction face enormous challenges. As such, a series of new and innovative technologies have been developed and applied in the planning and design which represent the highest level in the construction of underground roads in China today. This thesis focuses on such challenges and new technologies encountered and applied in the design of Shanghai North Bypass Road with an aim to provide reference to the construction of other underground roads in the downtown area.